Identifikasi Orchid Mycorrhiza Pada Akar Anggrek Dendrobium nobile - Arsitalia, Metari; Wahyudi; Bambang Irawan; Mahfut (UNIVERSITAS PGRI MADIUN, 2023)
Orchid mycorrhiza is a type of fungus that is able to associate well with orchid plants. Orchids require fungal hyphae infection at every phase of their growth and development. Mycorrhizal fungi provide the organic and organic nutrients needed by orchid planting. Meanwhile, orchid plants are suppliers because the results of photosynthesis of orchid plants are distributed in the body of fungi as an energy source. Given the importance of the prospect of mycorrhizal utilization for orchids, it is necessary to continue to develop studies on identification. The purpose of this study is to isolate, identify and characterize mycorrhiza in Dendrobium nobile orchids. The method used was with a descriptive design on the identified orchids, samples in the form of Dendrobium nobile orchid roots, the media used was PDA media, transverse and longitudinal root cut types.Â The way it works includes sample preparation, media preparation, fungal isolation, fungal colony purification,